Brzina nastanka i intenzitet znakova trovanja organofosfatnim jedinjenjima u odnosu na dozu paraoksona i preživljavanje pacova - Maksimović, Žana M; Duka, Dajana; Bednarčuk, Nataša; Škrbić, Ranko; Stojiljković, Miloš P (Scripta Medica, 2021)
Introduction: Oganophosphorus compounds (OP) bind to acetylcholinesterase (AChE) and inactivate it. In the synaptic cleft, undestroyed and accumulated acetylcholine produce the acute cholinergic effects. The aim of this study was to determine the frequency, speed of onset and intensity of certain signs of paraoxon poisoning depending on dose and outcome of poisoning. Methods: The study was conducted in adult Wistar rats. The median lethal dose (LD50) of paraoxon as well as protective ratio (PR) of atropine (10 mg/kg intramuscularly) was determined. Clinical signs of poisoning were observed: fasciculations, tremor, seizures, ataxia, piloerection, lacrimation, exophthalmos, bizzare/stereotypic behaviour and dyspnoea. The time from paraoxon injection to the first appearance of the sign of poisoning was recorded as well as the intensity of poisoning with evaluation at 10 time intervals throughout the 4 h observational period. Results: The LD50 of paraoxon was 0.33 mg/kg (subcutaneously) and PR of atropine was 2.73. Dose-dependent, piloerection occurred more often (p = 0.009) and at higher intensity (p = 0.016) at higher doses. Fasciculations, tremor, seizures and ataxia occurred significantly earlier at higher doses of paraoxon (p = 0.015, 0.002, 0.021 and 0.016, respectively), as well as the intensity of seizure, tremor and fasciculation. Piloerection (p = 0.002) and seizures occurred more frequently (p = 0.009) in non-survivors. Fasciculations, tremor, seizures and ataxia occurred significantly earlier and at higher intensity in non-survivors (p < 0.001, for all parameters), as well as dyspnoea (p = 0.009 and p = 0.048). In atropine-protected rats, nicotinic effects persevered, so they were the prognostic parameter of the severity of the poisoning. Conclusion: Seizures and fasciculations followed by tremor were strong prognostic parameters of the probability of lethal outcome of paraoxon poisoning. Also, the mentioned poisoning signs were with their intensity and speed of occurrence in a clear positive correlation with the administered dose of paraoxon. Even at high doses of paraoxon, atropine blocked the muscarinic (but not nicotinic) effects and somewhat mitigated the CNS toxic effects.